Design and Pro-typing of an Electronic Coil Winding Machine. - Arinaitwe, Joel (Kabale University, 2024)
Frequently, putting the driven equipment back in service is the highest priority, and users have made their decisions based on speed and initial cost. In the past, electrical power was very inexpensive, so managers were not concerned if the rewound motor was less efficient and cost more to Industries. Though method used to do motor repair in industries is motor rewinding which is a way of repairing spoilt motors in the industries which quite as few experienced technicians in charge and it takes a long period of time to carry out a motor rewinding process. This project introduces an electronic coil winding machine that addresses these limitations. The machine will employ an encoder, a rotary sensor that translates rotational motion into electrical signals. This allows for: Precise Control: The encoder data can be used by a control system to precisely regulate the speed and direction of the winding spindle, ensuring consistent coil geometries. Accurate Counting: The encoder pulses directly correlate to the number of wire rotations, providing a highly accurate measurement of the number of windings. Data Recording and Analysis: The encoder data can be logged and analyzed to monitor the winding process, identify potential issues, and optimize machine parameters for different coil specifications.